Case Report: Five-Level Unilateral Laminectomy Bilateral Decompression (ULBD) by Two-Stage Unilateral Biportal Endoscopy (UBE) - Wang, Wen-long; Liu, Zheng; Wu, Si-jun (Frontiers in Surgery, 2022)
Introduction Unilateral biportal endoscopy (UBE) is a relatively new yet common minimally invasive procedure in spine surgery, capable of achieving adequate decompression for lumbar spinal stenosis through unilateral laminectomy bilateral decompression (ULBD). Neither additional fusion nor rigid fixation is required, as UBE-ULBD rarely causes iatrogenic lumbar instability. However, to our knowledge, five-level ULBD via two-stage UBE without lumbar fusion has been yet to be reported in the treatment of multilevel lumbar spinal stenosis. Case description We present a case of an 80-year-old female patient who developed progressive paralysis of the lower extremities. Radiographic examinations showed multilevel degenerative lumbar spinal stenosis and extensive compression of the dural sac and nerve roots from L1-2 to L5-S1. The patient underwent five-level ULBD through two-stage UBE without lumbar fusion or fixation. One week after the final procedure, the patient could ambulate with walking aids and braces. Moreover, no back pain or limited lumbar motion was observed at the 6-month follow-up. Conclusion Multilevel ULBD through UBE may provide elderly patients with an alternative, minimally invasive procedure for treating spinal stenosis. This procedure could be achieved by staging surgeries. In this case, we reported complaints of little back pain, despite not needing to perform lumbar fusion or fixation.